Penegakan Hukum Sanksi Administrasi Terhadap Pelaku Usaha Rumah Makan yang Melanggar Protokol Kesehatan dalam Masa Pandemi Coronavirus Disease 2019 di Kota Serang - Rafli Aulia; Rila Kusumaningsih (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2021)
World Health Organization (WHO) declared Coronavirus Disease 2019 (Covid-19) as a pandemic in early March 2020. The spread of Covid-19 does not only have an impact on health aspects, but also on political, economic, social and cultural aspects. To restore economic growth, the Government issued a new normal policy (new normal order). To prevent and control Covid-19, the Serang City Government stipulates Serang Mayor Regulation Number 30 of 2020 concerning the Implementation of Discipline and Law Enforcement of Health Protocols as an Efforts to Prevent and Control Coronavirus Disease 2019. The author is interested in researching how to enforce administrative sanctions on business actors. restaurants that violate health protocols during a pandemic in Serang City based on Serang Mayor Regulation Number 30 of 2020? and what are the factors that are obstacles in enforcing administrative sanctions against restaurant business actors who violate health protocols during the pandemic in Serang City based on Serang Mayor Regulation Number 30 of 2020?.This study uses an empirical juridical research method by taking a case approach and a statutory approach. The data used in this study is secondary data supported by primary data in the form of interviews with the Serang City Satpol PP, which were then analyzed descriptively qualitatively.The results of the study show that the enforcement of administrative sanctions for business actors who violate health protocols during the Covid-19 pandemic in Serang City has been carried out according to Perwalkot Serang Number 30 of 2020. Sanctions are given to restaurant business actors who violate health protocols during the pandemic. Covid-19, namely sanctions in the form of verbal warnings or written warnings and temporary suspension of operations, as stipulated in Article 7 letter b paragraphs (1) and (2) Mayor Regulation Number 30 of 2020. As for the obstacles for the Serang City Satpol PP in implementing enforcement Administrative sanctions law is in the form of lack of facilities and facilities and weak legal awareness of the people of Serang City.